Outcast dragon secrets - Golden, Christopher (Scholastic Inc., 2005)
Timothy ... a villain? After learning how his powerlessness can be used as a weapon in the world of magic and defeating Nicodemus's plan to overthrow the government, Timothy travels to a war-torn dimension to help the Wurm, fierce magicians and warriors descended from an ancient dragon race. But while covertly gathering information on the age-old feud between the bloodthirsty Wurm and the Parliament of Mages, Timothy discovers a very different story -- one of peaceful Wurms and a conspiracy led by the Parliament of Mages. But that's not the only problem on Timothy's hands. The mysterious girl he spotted in SkyHaven is the granddaughter of Nicodemus, and she's challenging Leander's right to be Grandmaster of the Order of Alhazred. And despite Nicodemus's death, mages are still disappearing-and this time someone is painting Timothy as the villain.